2021
DOI: 10.3390/microorganisms9020432
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal Communities on Skin Are Associated with Atopic Dermatitis and Disease Severity

Abstract: The skin microbiota of atopic dermatitis (AD) patients is characterized by increased Staphylococcus aureus colonization, which exacerbates disease symptoms and has been linked to reduced bacterial diversity. Skin bacterial communities in AD patients have mostly been described at family and genus levels, while species-level characterization has been limited. In this study, we investigated the role of the bacteria belonging to the Staphylococcus genus using targeted sequencing of the tuf gene with genus-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 64 publications
5
38
0
1
Order By: Relevance
“…Generally, the most severely injured tissue is often accompanied by higher bacterial density (7)(8)(9). Cattle infected with bovine PmA usually exhibits serious pneumonia in clinic, and it was found that profuse growth of bovine PmA existed in the bovine lungs (10).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the most severely injured tissue is often accompanied by higher bacterial density (7)(8)(9). Cattle infected with bovine PmA usually exhibits serious pneumonia in clinic, and it was found that profuse growth of bovine PmA existed in the bovine lungs (10).…”
Section: Introductionmentioning
confidence: 99%
“…Data from a previously published cohort of 92 healthy community-dwelling adults (referred to as nonexposed) recruited at the Danish national blood donor clinic at Hvidovre Hospital, Copenhagen, Denmark, in May 2019 and January 2020 were included in the study ( 35 ). Samples were collected at the anterior nares once (by rotating the swab three times in one nostril).…”
Section: Methodsmentioning
confidence: 99%
“…Similar observations have been made on the free fatty acids and ceramides in the stratum corneum of Netherton syndrome [ 94 ]. The skin of subjects with atopic dermatitis tends to become colonized with Staphylococcus aureus [ 95 ]. This represents a risk for infection and may reflect the fact that both free sphingosine and sapienic acid are below normal levels in atopic skin [ 96 , 97 ].…”
Section: Skin Disease and The Barriermentioning
confidence: 99%